Diferenciación de especies argentinas de Clinopodium (Lamiaceae: Nepetoideae) a través de caracteres morfológicos y anatómicos de sus frutos - Scandaliaris, Melina (2013)
Differentiation of Argentinean Clinopodium (Lamiaceae: Nepetoideae) species through morphological and anatomical fruits characters. An integral study of fruits belonging to native Argentinean species of Clinopodium (Lamiaceae: Nepetoideae: Mentheae: Menthinae) has been made with the following aims: a) to characterize its exomorphology and anatomy; b) to correlate the pericarp structure with the phenomenon of the myxocarpy; c) to assess the incidence of the carpological characters to differentiate the species. Observations have been carried out using light and scanning electron microscope. Shape, size, surface ornamentation, indumentum and shape of abscission scar were the most diagnostic value features. Myxocarpy was proved in the genus but this phenomenon is not consistent in all the studied species. The pericarp structure revealed two anatomical patterns, each one associated with the production of mucilage, whereas the outer region of the mesocarp varies according to the species. Some taxonomical considerations have been discussed.